Two new Gomphonema species (Bacillariophyta) from the Maritime Antarctic Region - Vijver, Bart Van De; Kopalová, Kateřina; Zidarova, Ralitsa; Kociolek, J. Patrick (Phytotaxa, 2016)
Two new diatom taxa belonging to the genus Gomphonema were recorded during a survey of the Maritime Antarctic freshwater and limno-terrestrial diatom flora: Gomphonema jamesrossense sp. nov. and G.maritimo-antarcticum sp. nov. Detailed light (LM) and scanning electron microscope (SEM) observations are used to characterize the morphology and ultrastructure of the two new Gomphonema taxa. Comparisons with similar taxa and the ecological preferences of each species are added. The revision of these species confirmed the endemic nature of the Antarctic diatom flora.